Study the energy recovery in acrylic boiler - Ummu Atirah , Hanipah (2012)
Boiler is widely used in industry as a utility which generate steam or hot water in a plant. Since, boiler involve heat exchange in the process, thus, it will involve energy loss in boiler. The loss can be caused by flue gas, surface radiation and convection and also because of blow down process. Therefore, this study is aimed to study the energy recovery of Acrylic Boiler. About 24% energy lost in this boiler. Thus, energy balance will be constructed by considering first law thermodynamics, calculating the energy loss based on flue gas stream based on ASME formulae and minimizing the energy loss. 77% of the losses due to flue gas lost. Heat recovery to minimize the lost will be considered. The recovered heat is used to preheat the boiler feed water until 93.3 °C. The loss can be minimized efficiently until 64%. Besides, the boiler efficiency is increased significantly. Hence superheated steam generated also can be increased up to 11%. Economic analysis should be done as to compare the effectiveness of heat recovery and energy saving for the boiler system.